(untitled) (Journal of the College of Basic Education, 2022)
The research consists of five chapters as follows:The first DoorThe research problem includes that extra-curricular sporting events receive great attention from officials and specialists in the field of school extra-curricular sporting events. Secondary schools with the aim of extracting field results that can be used to develop the practice of school extra-curricular sports activities in general.